Assessment of adherence to therapy and exploring of barriers and facilitators in HIV positive patients in Tabriz-Iran: a mixed method study protocol - Amin Ghanbari; Maryam Ordibeheshti Khiaban; Armin Aslani; Amir Reza Faraji; Milad Mohammadi; Azita Fathnezhad Kazemi (BMC, 2019)
Abstract Background Adherence to therapy is a key predictor of the success of human immunodeficiency virus (HIV) treatment. There is limited information available from Iran about that and there is a need for more knowledge about factors influencing treatment adherence. The aim of this study is to examine adherence levels and to explore patients' views about barriers and facilitators to HIV treatment adherence. Methods This mixed-method study with the sequential explanatory design has two phases. The first phase (quantitative phase) is a cross- sectional study to assess the in Tabriz, the sixth large city of Iran. A convenience sampling method will be used to select 150 HIV positive patients who visit health centers in Tabriz. The second phase is a qualitative study designed to explore the HIV positive patients' views of barriers and facilitators that can affect their adherence to therapy. In this phase, purposive sampling and in-depth individual interviews will be conducted for data collection. The conventional content analysis approach will be employed for data analysis. In addition to literature review and nominal group technique, the findings of the qualitative and quantitative phases, will be used to recommend some strategies to support adherence to therapy in HIV positive patients. Discussion This is the first study looking into adherence to therapy and exploring of factors influencing in HIV positive patients which will be performed via a mixed-method approach, aiming to develop health practices improvement strategies. It is worth noting that there is no strategic guideline in Iran's health system for improvement of treatment adherence in HIV positive patients. Health professionals and policy makers can be aware of factors influencing HIV treatment adherence. Therefore, it is hoped that the strategy proposed in the current study can lead to improvements their ability to treatment adherence.